2001
DOI: 10.1046/j.1365-294x.2001.t01-1-01405.x
|View full text |Cite
|
Sign up to set email alerts
|

Glacial biogeography of North American coho salmon (Oncorhynchus kisutch)

Abstract: To study the glacial biogeography of coho we examined 20 microsatellite loci and mitochondrial DNA D-loop sequence in samples from Alaska to California. Microsatellite data divided our samples among five biogeographic regions: (1) Alaska and northern coastal British Columbia; (2) the Queen Charlotte Islands; (3) the mainland coast of British Columbia and northern Washington State; (4) the Thompson River; and (5) Oregon and California. The D-loop sequence data suggested three geographical regions: (1) Oregon an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
54
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 68 publications
6
54
0
2
Order By: Relevance
“…It is not known if, or to what extent, Pacific salmon occupied the region during glaciation. However, there is evidence some salmon populations in the area may have survived the last glaciation in small numbers (e.g., Smith et al 2001). The general geographic congruence among species r 2 is the posterior mode of unexplained variance associated with each model and the 95% HPDI is the 95 percent highest probability interval.…”
Section: Discussionmentioning
confidence: 99%
“…It is not known if, or to what extent, Pacific salmon occupied the region during glaciation. However, there is evidence some salmon populations in the area may have survived the last glaciation in small numbers (e.g., Smith et al 2001). The general geographic congruence among species r 2 is the posterior mode of unexplained variance associated with each model and the 95% HPDI is the 95 percent highest probability interval.…”
Section: Discussionmentioning
confidence: 99%
“…Yukon and Alaska) and to the south (i.e. southern Washington) of BC (Smith et al, 2001). Island biogeography theory indicates that large, continuous zones have more species than small, fragmented zones (MacArthur and Wilson, 1967).…”
Section: Discussionmentioning
confidence: 99%
“…As expected for Pacific Northwest salmon populations [46] and for restricted time period from which the samples obtained, low sequence variations were observed for all amplified PCR sequences. Studies of both ancient and modern salmon have suggested that these low levels of genetic diversity may reflect the relatively recent post-glacial recolonization of these species [32,40,44,46]. Only one haplotype was identified within each of the species for the three amplified fragments, with the exception of the Cyt B amplifications of chinook remains which yielded two haplotypes (distinguished by only a single base pair difference e see Figs.…”
Section: Pcr Amplificationsmentioning
confidence: 99%